KEANEKARAGAMAN JENIS POHON PENYUSUN ARBORETUM KONSERVASI HUTAN HUJAN TROPIS PT ASMIN BARA BRONANG KABUPATEN KAPUAS KALIMANTAN TENGAH - Siti Maimunah; Hasan Mudzakir; Mohammad Sopan; Jay H. Samek (Lambung Mangkurat University-Indonesia, 2020)
The arboretum area is inside the concession area in Barunang Village, Kapuas Regency, Central Kalimantan, which is in the heath forest area towards the lowland forest. Arboretum area 28 ha with a elevation on 114 mdpl.The research methodology uses a modified version of the Biodiversity Assessment Tool originally developed by the High Conservation Values Resource Network (HCVRN) and the World Wildlife Fund (WWF). The method developed by USAID LESTARI and the University Consortium together with Michigan State University USA.The results showed that there were 29 arboretum tree compilers which were dominated by Myrtaceae family of 36 tree species, 32 species of Dipterocarpaceae and 20 species of Myristicaceae which were distributed in groups according to the topography and associated species associations. Species Richness 93; Menhinick's Richness Index 5.57; Margalef Richness Index 16.34; Shannon Sspecies Diversity index 4.07, Simpson Diversity Index 0.98; type evenness index 0.90; Most Abundance Species is Jambu-jambu B (Syzygium spp. B) 3.30 and Importance Values Index with dominan species is Tagaron ( Crataeva adansonii) 7.51. This arboretum area is a secondary forest area that has been cleared in several parts which can be maximized in its management with various methods for saving nature, recreation, education and research and other zones including animal breeding.